Assistance in making corn silk juice for the Family Welfare Empowerment Group in Giripurno Village - Siti Rofiatul Sazjiyah; Racmad Kristiono Dwi Susilo; Luluk Dwi Kumalasari (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Giripurno Village is one of the villages that has the largest corn agricultural commodity in Batu City. The abundance of corn harvests makes prices unstable. In addition, most farmers sell their corn harvest in the form of corn kernels, so it is not optimal in processing corn cobs, husks, and silk. Most of the people belong to the low economy. The community service program aims to provide ideas through assistance to the Family Welfare Empowerment Group (PKK) to process corn silk waste into drinks that have economic potential for the community. The assistance method used is in the form of training in making drinks, packaging, and selling. The evaluation was carried out to determine the improvement of skills in making corn silk juice drinks. This assistance program was attended by 15 participants. The results of the assistance showed that PKK women had understood how to process corn silk. This is evidenced by the fact that sales have reached 468 products sold in several cities, especially East Java. Hence, it is concluded that the assistance of this corn silk drink, can improve the welfare of the local community.